Microglia-derived CCL2 has a prime role in neocortex neuroinflammation - Mariella Errede; Tiziana Annese; Valentina Petrosino; Giovanna Longo; Francesco Girolamo; Ignazio de Trizio; Antonio d’Amati; Antonio Uccelli; Nicole Kerlero de Rosbo; Daniela Virgintino (Fluids and Barriers of the CNS, 2022)
Abstract Background In myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE), several areas of demyelination are detectable in mouse cerebral cortex, where neuroinflammation events are associated with scarce inflammatory infiltrates and blood–brain barrier (BBB) impairment. In this condition, the administration of mesenchymal stem cells (MSCs) controls neuroinflammation, attenuating astrogliosis and promoting the acquisition of stem cell traits by astrocytes. To contribute to the understanding of the mechanisms involved in the pathogenesis of EAE in gray matter and in the reverting effects of MSC treatment, the neocortex of EAE-affected mice was investigated by analyzing the cellular source(s) of chemokine CCL2, a molecule involved in immune cell recruitment and BBB-microvessel leakage. Methods The study was carried out by immunohistochemistry (IHC) and dual RNAscope IHC/in situ hybridization methods, using astrocyte, NG2-glia, macrophage/microglia, and microglia elective markers combined with CCL2. Results The results showed that in EAE-affected mice, hypertrophic microglia are the primary source of CCL2, surround the cortex neurons and the damaged BBB microvessels. In EAE-affected mice treated with MSCs, microgliosis appeared diminished very soon (6 h) after treatment, an observation that was long-lasting (tested after 10 days). This was associated with a reduced CCL2 expression and with apparently preserved/restored BBB features. In conclusion, the hallmark of EAE in the mouse neocortex is a condition of microgliosis characterized by high levels of CCL2 expression. Conclusions This finding supports relevant pathogenetic and clinical aspects of the human disease, while the demonstrated early control of neuroinflammation and BBB permeability exerted by treatment with MSCs may have important therapeutic implications.